SINTESIS BIOMATERIAL HYDROXYAPATITE DENGAN PROSES FLAME SPRAY PYROLYSIS DISERTAI PENAMBAHAN ADITIF ORGANIK - Adhi Setiawan; W Widiyastuti; Sugeng Winardi; Agung Nugroho (Reaktor, 2016)
SYNTHESIS OF HYDROXYAPATITE BIOMATERIALS BY FLAME SPRAY PYROLYSIS PROCESS WITH ADDITION OF ORGANIC ADDITIVES. Hydroxyapatite is  biomaterial which is widely used for biomedical aplication such as implant because  biocompatible, bioactivity, and strong affinity to biopolymers. Therefore parameters of morphology and crystallinity becomes an important parameter to be controlled. The addition of the organic additive on HAp precursor with ethylene glycol, polyethylene glycol 400, and urea is the alternative to improve the size, morphology, and crystallinity of HAp particles. The equipment for flame spray pyrolysis process includes ultrasonic nebulizer, flame reactor, and eletrostatic precipitator. The amount of organic additives used in experiment is  30%, 50%, and 100% by mass of the precursor. The result of SEM and XRD showed HAp synthesized by the addition of additive material has a smaller size than without using the additive and crystallinity is better than no additive. In addition HAp synthesized by the addition of 30% PEG additive have smallest average particle size about 114 nm, crystalite size about 16,6 nm and spherical morphology with a low agglomeration. Keywords: Hidroxyapatite, organic additives, flame spray pyrolysis, morfology  Abstrak Hydroxyapatite merupakan biomaterial yang seringkali diaplikasikan dalam biomedis sebagai bahan implant karena sifatnya yang biocompatible, bioactivity, dan memiliki afinitas yang kuat terhadap biopolimer. Oleh karena itu parameter morfologi serta kristalinitas partikel menjadi parameter penting untuk dikontrol. Penambahan aditif organik pada prekursor HAp dengan etilen glikol, polietilen glikol 400, serta urea merupakan alternativ agar memperbaiki ukuran, morfologi, serta meningkatkan kristalinitas partikel HAp. Peralatan utama flame spray pyrolysis meliputi ultrasonic nebulizer, reaktor flame, dan eletrostatik precipitator. Jumlah aditif organik yang digunakan pada eksperimen antara lain 30%, 50%, dan 100% massa prekursor. Hasil SEM dan XRD menunjukkan bahwa HAp yang disintesis dengan penambahan bahan aditif memiliki ukuran lebih kecil daripada tanpa menggunakan aditif dan tingkat kristalinitasnya lebih baik dibandingkan tanpa aditif. Selain itu HAp yang disintesis dengan penambahan aditif PEG sebanyak 30% memiliki ukuran rata-rata partikel yang terkecil yaitu sebesar 114 nm dengan ukuran kristal mencapai 16,6 nm serta memiliki morfologi bulat dengan tingkat aglomerasi yang rendah.